Stabilizing Grain Yield and Nutrition Quality in Purple Rice Varieties by Management of Planting Elevation and Storage Conditions - Supapohn Yamuangmorn (Agronomy, 2021)
Purple rice has become an interesting source of nutritional value among healthy cereal grains. The appropriate cultivation together with post-harvest management would directly benefit farmers and consumers. This study aimed (i) to determine the yield, grain nutritional quality, and antioxidant capacity of purple rice varieties grown at lowland and highland elevations, and (ii) to evaluate the effects of storage conditions on the stability of the rice nutritional value during six months of storage. The high anthocyanin PES variety grown in the lowlands had a higher grain yield than the plants grown in the highlands, but grain anthocyanin concentration had the opposite pattern. In the high antioxidant capacity KAK variety, grain yield and DPPH activity were not significantly different between plants grown at the two elevations. The storage of brown rice and vacuum-sealed packages were both found to preserve greater anthocyanin concentrations in PES, but there was no effect on the DPPH activity of KAK. The grain properties were not significantly different between storage at 4 °C and room temperature. This study suggests that the optimal cultivation practices and storage conditions would result in the higher yield and grain quality of purple rice varieties.